If $y=\sqrt{\frac{1-\sin 2x}{1+\sin 2x}}$, prove that $\frac{dy}{dx}+\sec^2(\frac{\pi}{4}-x)=0$

My attempts:

Attempt 1:

$y=\sqrt{\frac{1-\sin 2x}{1+\sin 2x}}$

$\implies y=\sqrt{\frac{\sin^2 x+\cos^2 x-2\sin x \cos x}{\sin^2 x+\cos^2 x+2\sin x \cos x}}$

$\implies y=\sqrt{\frac{(\sin x -\cos x)^2}{(\sin x+\cos x)^2}}$

$\implies y=\frac{\sin x -\cos x}{\sin x +\cos x}$

$\therefore \frac{dy}{dx}=\frac{(\sin x +\cos x)(\cos x+\sin x)-(\sin x -\cos x)(\cos x -\sin x)}{(\sin x +\cos x)^2}$

$\implies \frac{dy}{dx}=\frac{(\sin x+\cos x)^2+(\sin x -\cos x)^2}{(\sin x+\cos x)^2}$

$\implies \frac{dy}{dx}=\frac{2(\sin^2 x+\cos^2 x)}{(\cos(\frac{\pi}{2}-x)+\cos x)^2}$

$\implies \frac{dy}{dx}=\frac{2}{(2\cos(\frac{\pi}{4})\cos(\frac{\pi}{4}-x))^2}$

$\implies \frac{dy}{dx}=\frac{2}{4\cos^2(\frac{\pi}{4})\cos^2(\frac{\pi}{4}-x)}$

$\implies \frac{dy}{dx}=\frac{2}{4\times\frac{1}{2}\cos^2(\frac{\pi}{4}-x)}$

$\implies \frac{dy}{dx}=\sec^2(\frac{\pi}{4}-x)$

$\implies \frac{dy}{dx}-\sec^2(\frac{\pi}{4}-x)=0$

But i have to prove $\frac{dy}{dx}+\sec^2(\frac{\pi}{4}-x)=0$

Attempt 2:

$y=\sqrt{\frac{1-\sin 2x}{1+\sin 2x}}$

$\implies y=\sqrt{\frac{\cos^2 x+\sin^2 x-2\cos x \sin x}{\cos^2 x+\sin^2 x+2\cos x \sin x}}$

$\implies y=\sqrt{\frac{(\cos x -\sin x)^2}{(\cos x+\sin x)^2}}$

$\implies y=\frac{\cos x -\sin x}{\cos x +\sin x}$

$\therefore \frac{dy}{dx}=\frac{(\cos x +\sin x)(-\sin x-\cos x)-(\cos x -\sin x)(-\sin x +\cos x)}{(\cos x +\sin x)^2}$

$\implies \frac{dy}{dx}=\frac{-(\cos x+\sin x)^2+(\cos x -\sin x)^2}{(\cos x+\sin x)^2}$

$\implies \frac{dy}{dx}=\frac{(\cos x -\sin x)^2-(\cos x+\sin x)^2}{(\cos x+\sin x)^2}$

$\implies \frac{dy}{dx}=\frac{-4\sin x\cos x}{(\cos x+\cos(\frac{\pi}{2}-x))^2}$

$\implies \frac{dy}{dx}=\frac{-4\sin x\cos x}{(2\cos(\frac{\pi}{4})\cos(x-\frac{\pi}{4}))^2}$

$\implies \frac{dy}{dx}=\frac{-4\sin x\cos x}{4\cos^2(\frac{\pi}{4})\cos^2(x-\frac{\pi}{4})}$

$\implies \frac{dy}{dx}=\frac{-4\sin x\cos x}{4\times \frac{1}{2}\cos^2(x-\frac{\pi}{4})}$

$\implies \frac{dy}{dx}=\frac{-2\sin x\cos x}{\cos^2(x-\frac{\pi}{4})}$

Attempt 3:

$y=\sqrt{\frac{1-\sin 2x}{1+\sin 2x}}$

$\implies y=\sqrt{\frac{(1-\sin 2x)(1-\sin 2x)}{(1+\sin 2x)(1-\sin 2x)}}$

$\implies y=\frac{1-\sin 2x}{\cos 2x}$

$\therefore \frac{dy}{dx}=\frac{\cos 2x(-2\cos 2x)-(1-\sin 2x)(-2\sin 2x)}{\cos^2 2x}$

$\implies \frac{dy}{dx}=\frac{-2\cos^2 2x+2\sin 2x(1-\sin 2x)}{\cos^2 2x}$

My questions:

(i) Why does Attempt 2 give a result different from that given by Attempt 1.

(ii) How do i prove the result?

  • $\begingroup$ (i) Actually $\sqrt{a^{2}} = |a|$. You have considered in attempts 1 and 2 just a single case ($a$ and $-a$, repectively). (ii) You should consider both cases. $\endgroup$ – Alex Silva Jun 9 '18 at 6:51
  • $\begingroup$ When you got to the step $ y =\dfrac{\cos(x) -\sin(x)}{\cos(x)+\sin(x)}$ , divide both numerator and demoninator by $\cos(x)$, it'll be easier as you'll get the result in terms of $\tan$ $\endgroup$ – The Integrator Jun 9 '18 at 6:55

The statement that you are trying to prove is not true for every $x$. If it was, we would always have $\frac{\mathrm dy}{\mathrm dx}\leqslant0$ and therefore $y$ would be decreasing. But it is increasing in $\left[\frac\pi4,\frac\pi2\right]$, for instance.

The statement holds in $\left(-\frac\pi4,\frac\pi4\right]$. Yours first attempt proves it, as long as you correct this mistake: what you deduce from the equality$$y=\sqrt{\frac{(\sin x-\cos x)^2}{(\sin x+\cos x)^2}}$$is that$$y=\frac{-\sin x+\cos x}{\sin x+\cos x},$$since $y$ is a square root and therefore $y\geqslant0$.


"Why does Attempt 2 give a result different from that given by Attempt 1."

Your mistake is that You conclude $\sqrt{a^2}=a$. Actually, one time You conclude that $\sqrt{a^2}=a$ and another time that $\sqrt{(-a)^2}=-a$ although $\sqrt{a^2}$ and $\sqrt{(-a)^2}$ are the same. Correct would be $\sqrt{a^2}=\pm a$, so two values.

"(ii) How do i prove the result?"

You don't need to do any transformation of the kind, You can directy differentiate the given expression.


In fact, the result you want is not true: it depends on the values of $x$.

Having said this, with a small modification, any of your methods should work. I'll use your third method. Note that you have $$y=\sqrt{\frac{(1-\sin2x)^2}{\cos^22x}}\ ;$$ this gives $$y=\left|\frac{1-\sin2x}{\cos2x}\right|\ ,$$ and the omission of the absolute values is your main problem.

First, suppose that $-\pi/4<x<\pi/4$. Then $1-\sin2x>0$ and $\cos2x>0$; so $$y=\frac{1-\sin2x}{\cos2x}\ .$$ Your differentiation is correct, and you can continue $$\eqalign{\frac{dy}{dx} &=\frac{-2\cos^2 2x+2\sin 2x(1-\sin 2x)}{\cos^2 2x}\cr &=\frac{2\sin2x-2}{\cos^22x}\cr &=-2\,\frac{1-\sin2x}{1-\sin^22x}\cr &=-\frac2{1+\sin2x}\cr &=-\frac2{1+\cos(\frac\pi2-2x)}\cr &=-\frac1{\cos^2(\frac\pi4-x)}\cr &=-\sec^2\Bigl(\frac\pi4-x\Bigr)\cr}$$ which is what you want.

If, however $\pi/4<x<3\pi/4$, then $1-\sin2x>0$ and $\cos2x<0$; so $$y=-\frac{1-\sin2x}{\cos2x}$$ and exactly the same working will give $$\frac{dy}{dx}=\sec^2\Bigl(\frac\pi4-x\Bigr)\ .$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.